Icariin modulates osteogenic and adipogenic differentiation in ADSCs via the Hippo-YAP/TAZ pathway: a novel therapeutic strategy for osteoporosis - Shaozi Lin; Zuyu Meng; Mei Wang; Zixuan Ye; Mengsha Long; Yiyao Zhang; Fang Liu; Hongling Chen; Menghan Li; Jiajia Qin; Haiquan Liu (Frontiers in Pharmacology)
BackgroundAdipose-derived stem cell (ADSC) transplantation presents a promising approach for osteoporosis (OP) treatment. However, the therapeutic efficacy of ADSCs is hindered by low post-transplantation survival rates and limited capacities for adhesion, migration, and differentiation. Icariin (ICA), the primary active compound of Epimedium, has been shown to promote cell proliferation and induce osteogenic differentiation; however, its specific effects on ADSC osteogenesis and the mechanisms by which ICA enhances osteoporosis treatment through cell transplantation remain inadequately understood.PurposeThis study investigates the effects of different concentrations of ICA on the osteogenic and adipogenic differentiation of rat ADSCs, aiming to elucidate the underlying mechanisms. ADSCs were isolated from female SPF-grade SD rats, with surface markers identified through flow cytometry. Osteogenic and adipogenic differentiation were assessed using Alizarin Red and Oil Red O staining, respectively. Third-generation ADSCs were divided into five groups: control, resveratrol (100 μmol/L), and four ICA treatment groups (1, 10, 50, and 100 μmol/L). Western blotting was performed to analyze the expression of factors associated with the Hippo-YAP/TAZ signaling pathway and the adipogenic marker PPARγ. Additionally, ADSCs were labeled with lentiviruses carrying enhanced green fluorescent protein (EGFP) and 5-bromo-2-deoxyuridine (BrdU) to assess their in vivo distribution, survival, proliferation, and differentiation of ADSCs post-ICA intervention.ResultsIn vitro, ICA significantly inhibited the Hippo pathway, reducing YAP and TAZ phosphorylation and enhancing their transcriptional activity, while simultaneously suppressing PPARγ. This promoted osteogenesis and inhibited adipogenesis in ADSCs. In vivo, ICA-treated ADSCs demonstrated effective distribution, survival, and osteogenic differentiation following subcutaneous injection into allogeneic rats.ConclusionOur study demonstrates that ICA significantly enhances the osteogenic differentiation of ADSCs while inhibiting adipogenesis, providing novel insights and therapeutic strategies for osteoporosis and related conditions.